Pengaruh Waktu Pasteurisasi Terhadap Cemaran Mikrobiologis dan Aktivitas Antioksidan Loloh Daun Pohpohan (Pilea trinervia Wight.) - Nabillah, Icha; Kencana Putra, I Nengah; Suparthana, I Putu (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 10 No 4 (2021): Jurnal ITEPA, 2021)
Loloh is one of the traditional beverages in Bali made from fresh leaves, root, stem, seeds or fruit without cooking treatment (cold process). Some studies showed that loloh in several area in Bali is not worth to consume because of high level of microbial contamination. This study aimed to determine the effect of pasteurization time to produce loloh pohpohan leaves with the best antioxidant activity and free from microbial contamination. This experiment used a Completely Randomized Design with 7 variations of pasteurization treatment time, namely 0, 10, 15, 20, 25 30 and 35 minutes. The treatment was repeated three time for obtain 21 experimental units. The data obtained were analyzed by analyze of variance and if the treatment had significant effect, then it was followed by Duncan Multiple Range Test (DMRT). The result of this study showed that pasteurization time has a very significant effect (P<0,01) on total microbial, total coliform and antioxidant activity. The best loloh treatment in this study was obtain with 20 minutes pasteurization time with the total plate count 0 CFU/mL (no microbes showed), negative coliform and antioxidant activity 58.39% with IC50 valued 1584.097 ppm, the color is neutral, the aroma is neutral, the taste was bitter and neutral and overall acceptance is neutral.